Harvesting and Evaluating Uptake Machropage Induced by Ciprofloxacin HCl-Alginate-Carrageenan Pulmosphere - Aqsha, Aulia Charis; Rahmadi, Mahardian; Hariyadi, Dewi Melani (IKIP Mataram, 2024)
Ciprofloxacin HCl-Alginate-Carrageenan Pulmosphere has emerged as a therapy for lung infections. Ciprofloxacin HCl-Alginate-Carrageenan Pulmosphere consists of Ciprofloxacin HCl, Sodium Alginate, Kappa Carrageenan, and CaCl2 made using the ionotropic gelation method with the aim of delivering the drug via inhalation. Ciprofloxacin HCl-Alginate-Carrageenan Pulmosphere exhibits good physical characteristics that can be further studied in vitro using alveolar macrophage cells. Alveolar macrophages demonstrate a high level of effectiveness in removing pathogenic microorganisms from the lungs. More than 80% of alveolar macrophages can be easily obtained through lung lavage for study. This research aims to determine the uptake of Ciprofloxacin HCl-Alginate-Carrageenan Pulmosphere by alveolar macrophages. The extraction of alveolar macrophage cells was carried out through the utilization of the BAL (Bronchoalveolar Lavage) method. Pulmosphere was labeled with a fluorescent dye, Rhodamine-B, for visualization. Uptake evaluation was performed using the Nikon Eclipse TS2R Inverted Microscope. The findings suggest that alveolar macrophages have the ability to uptake Ciprofloxacin HCl-Alginate-Carrageenan Pulmosphere. This research significantly enhances current knowledge by revealing previously unidentified variables. The results not only question established theories but also provide practical insights for the field of pharmaceutics. As a result, this study deepens our comprehension of certain aspects and sets the stage for future research in related domains.